2020
DOI: 10.1371/journal.pgen.1008607
|View full text |Cite
|
Sign up to set email alerts
|

RHS-elements function as type II toxin-antitoxin modules that regulate intra-macrophage replication of Salmonella Typhimurium

Abstract: RHS elements are components of conserved toxin-delivery systems, widespread within the bacterial kingdom and some of the most positively selected genes known. However, very little is known about how Rhs toxins affect bacterial biology. Salmonella Typhimurium contains a full-length rhs gene and an adjacent orphan rhs gene, which lacks the conserved delivery part of the Rhs protein. Here we show that, in addition to the conventional delivery, Rhs toxin-antitoxin pairs encode for functional type-II toxin-antitoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Several previously conducted studies have indicated that bacterial toxins can be co‐opted into intracellular functions (TA systems) or as extracellular polymorphic toxins (Zhang et al, 2012; Jamet & Nassif, 2015; Triplett et al, 2016; Harms et al, 2017; Stårsta et al, 2020). The results presented here indicate that TA systems can also be converted into extracellular T6SS effectors through action of insertion elements (and possibly other kinds of genetic changes), providing novel weapons in the bacterial armory to dominate during intense competition with co‐habiting bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Several previously conducted studies have indicated that bacterial toxins can be co‐opted into intracellular functions (TA systems) or as extracellular polymorphic toxins (Zhang et al, 2012; Jamet & Nassif, 2015; Triplett et al, 2016; Harms et al, 2017; Stårsta et al, 2020). The results presented here indicate that TA systems can also be converted into extracellular T6SS effectors through action of insertion elements (and possibly other kinds of genetic changes), providing novel weapons in the bacterial armory to dominate during intense competition with co‐habiting bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…ECL_RS07670-ECL_RS7700 genes form a putative polycistronic operon, and ECL_RS07695 codes for an Rhs toxin, which could be involved in bacteria–bacteria and bacteria–eukaryotic cell interactions, as it was reported for Dickeya dadantii and S . Typhimurium, respectively ( Koskiniemi et al, 2013 ; Starsta et al, 2020 ). Hence, DMEM components might mimic conditions that occur during the bacteria–cell host interaction and it would stimulate the transcription of ECL_RS07670-ECL_RS7700 operon in such conditions.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, deletion of the toxin genes resulted in limited intracellular survival within fibroblasts, based on survival assays, indicating the significance of the toxin genes in survival within such intracellular environments ( Lobato-Márquez et al., 2015 ). Relevance of a TA system in survival of S. Typhimurium is not new, as Type II TA modules have previously been suggested in S. Typhimurium persistence within macrophages ( Stårsta et al., 2020 ). However, this study highlights for the first time that Type I TAs are equally important in facilitating adaptation of S .…”
Section: Section 1: Type I Toxin Antitoxin Systemsmentioning
confidence: 93%